Ellus Desfila São Paulo : comunicação, consumo e memória na cidade-mídia - Costa, Filipe de Oliveira (2017)
This research has as its theme the fashion shows as communicational ambiences, consumption of memories, experiences and also spaces of performances. The theoretical object is related to the uses of places of memories of the city of São Paulo as a way of intensifying the communicative strategies for the consumption of the institutional discourse of the brand that circulates in each parade. The empirical objects are the Ellus brand parade, namely: Winter 2008, Summer 2012, Winter 2013, Winter 2014 and Winter 2016. The question that guided the research presupposes that fashion shows are already consecrated advertising strategies as a way of publicizing brand. But for this research these parades also behave as a process that communicates the city and its places of memory (spaces and characters) through the performance that the parade itself performs. We seek to investigate whether the parades so understood convert the memories into a strategy for the symbolic consumption of Ellus' institutional discourse, which translates as sophisticated, urban and transgressive. The general objective is to identify and analyze how Ellus brand fashion shows that use the city and its memories (spaces and characters) communicate and convert memory into a strategy for the symbolic consumption of the brand's institutional discourse. The specific objectives are: to recognize the strategies of the production of the symbolic consumption of the values ​​enunciated in the narrative of the advertising brand Ellus by means of the analysis of the selected parades (Winter 2008, Summer 2012, Winter 2013, Winter 2014, Winter 2016); to identify the places of memory of the city of São Paulo, its characters and the game that is established between the representations of memory and its characters presented in the selected parades; to analyze the parade as performance (gesture, body, soundtrack and the circumstances of its accomplishment, like time and space). The theoretical reference includes authors such as Maria Aparecida Baccega, Everardo Rocha, Don Slater, Ana Paula de Miranda, Mary Douglas, Baron Isherwood, Claudia Pereira, Andreas Huyssen, Michel Pollak, Pierre Nora, Monica Nunes, Iuri Lotman, Paul Zumthor, among others contribute to the discussions. As methodological procedures are carried out bibliographical research in authors of the semiotics of culture, memory, consumption and fashion, and documentary research in videos of the parades and institutional of Ellus and graphic pieces of advertising campaigns of the brand. In addition, we refer in speeches of journalists specialized in fashion news, who were relevant allied to some theoretical aspects. The research corpus includes the analysis of photographic images and frames of the parades (urban spaces, clothes, gestures, soundtracks, temporal marking and construction of the elements that mark the spaces of the parades like scenography, lighting). The results indicate that there are strategies to provide the symbolic consumption of the memories of the locations of the parades in a way that will result in the loyalty of brand clients and symbolic consumers of the repositioned memories not only of the city of São Paulo but also of large urban spaces according to the urban, transgressive and sophisticated institutional discourse of Ellus.